Social development and the international development strategy (UN Research Institute for social Development GenevaCH, 1979)
Examines the international consensus on development objectives; the contrasts between these objectives and actual trends; the reasons that are frequently given to explain divergence between goals and trends and questions of social policy in an international development strategy.
DC